Parental intentions and requests to provide pain care for their infants in neonatal intensive care units - Shimizu, Aya; Arimitsu, Takeshi; Harada, Kana; Ozawa, Mio (Frontiers in Pediatrics, 2025)
PurposeThe Japan Association of Neonatal Nursing evaluated the pain care provided by parents to their infants admitted to the neonatal intensive care unit (NICU). However, further collaborations with families based on family-centered care are necessary to clarify the parental intentions and requests regarding pain care for their infants. This study aimed to describe the experiences and content of nonpharmacological pain care provided by parents to their infants, the intentions and requests of parents regarding each type of recommended pain care (irrespective of whether they had provided pain care at the NICU), and the reasons for their hesitation to implement specific pain management methods.MethodsA total of 108 parents with NICU-hospitalized infants, including 66 (65.6%) infants with a birth weight of <1,000 g, voluntarily responded to an anonymous self-administered online electronic survey. Sociodemographic and clinical data were quantitatively analyzed.ResultsIn our study population, 30.6% (N = 33) had provided pain care to their infants, 56.5% (N = 61) hoped to provide pain care in the future, and 40.7% (N = 44) expected advice for pain care options from healthcare professionals (HCPs). Swaddling, facilitated tucking, and skin-to-skin contact were the most popular options (≥60%). By contrast, the use of sucrose and breastfeeding (both 13.0%), skin-to-skin contact (7%), and use of expressed breast milk and non-nutritive sucking (both 3.7%) were less frequently used due to indifference or doubts, lack of knowledge about pain care, differences between recommended pain care methods and parental values, and pain care methods being inappropriate for the child's condition.ConclusionsThis survey demonstrated that when parents provide pain care for their children in the NICU, they are required to make choices based on the advice and knowledge offered by HCPs, taking into account the diverse values of parents as well as the overall condition of their infant and their breastfeeding status. Therefore, we suggest that HCPs support parents in choosing not only the recommended care but also the most appropriate pain care for the condition of their infant.